A Pyramidal Coder using a Nonlinear Filter Bank - Queiroz, Ricardo L. de; Florencio, Dinei (ICASSP, 1996)
We propose a novel pyramidal coder, which resembles the general structure of a JPEG coder, but which uses a nonlinear transform to replace the DCT. The nonlinear transform is obtained by the hierarchical application of a median filter predictor at subsampled versions of the original signal. The transformed samples are grouped into square blocks and used to replace the DCT in the JPEG baseline coder. The Proposed coder shows several advantages: computation is greatly reduced compared to the DCT, image edges are better encoded, blocking is eliminated, and it allows lossless coding. Objective comparisons show the superiority of the proposed coder against both baseline and lossless JPEG.